Hydrochar Derived from Pennisetum setaceum for Congo Red Adsorption: A Low-Cost Bioadsorbent from Invasive Grass - Karvenia, Icha Aulia; Royani, Idha; Mohadi, Risfidian (Indonesian Journal of Environmental Management and Sustainability, 2025)
This study investigates the adsorption performance of hydrochar derived from Pennisetum setaceum (PS) through hydrothermal treatment at 250°C for various reaction times (1-4 hours) for the removal of Congo Red (CR) dye from aqueous solutions. The materials were characterized using FTIR, XRD, SEM–EDS, BET, and pHpzc analysis to evaluate changes in functional groups, crystallinity, morphology, elemental composition, and surface charge. FTIR spectra confirmed the presence of oxygen-containing functional groups (O-H, C=O, C-O-C, C-O), while XRD patterns indicated a transition from amorphous to partially crystalline structures, followed by re-amorphization at longer reaction times. SEM images revealed a progressive increase in porosity and surface roughness, accompanied by an increase in carbon content, as shown by EDS. BET analysis of HPS-4 further confirmed its mesoporous structure with a surface area of 9.316 m2/g, which supports enhanced adsorption performance. Adsorption experiments demonstrated that the optimum pH for CR removal by HPS-4 was 5, with a maximum capacity of 51.674 ± 5.468 mg/g. Kinetic studies followed the pseudo-first-order model, and equilibrium data fitted well with the Langmuir isotherm, indicating monolayer adsorption. Thermodynamic analysis showed the process was spontaneous and exothermic (?H° = ?44.07 kJ/mol). The proposed adsorption mechanism involves a combination of electrostatic attraction, hydrogen bonding, and ?–? interactions between CR molecules and the aromatic structure of hydrochar. However, regeneration tests indicated a significant decrease in efficiency after the third cycle. These findings suggest that hydrochar from Pennisetum setaceum is a promising adsorbent for anionic dye removal, with optimal performance achieved under controlled hydrothermal conditions.